1988
DOI: 10.1152/jappl.1988.65.6.2545
|View full text |Cite
|
Sign up to set email alerts
|

Operation Everest. II: Nutrition and body composition

Abstract: Progressive body weight loss occurs during high mountain expeditions, but whether it is due to hypoxia, inadequate diet, malabsorption, or the multiple stresses of the harsh environment is unknown. To determine whether hypoxia due to decompression causes weight loss, six men, provided with a palatable ad libitum diet, were studied during progressive decompression to 240 Torr over 40 days in a hypobaric chamber where hypoxia was the major environmental variable. Caloric intake decreased 43.0% from 3,136 to 1,78… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
157
2

Year Published

1996
1996
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 190 publications
(170 citation statements)
references
References 0 publications
11
157
2
Order By: Relevance
“…It is noteworthy that similar results were obtained in EDL muscle (data not shown). Thus, in agreement with previous studies (4,33), these data show that hypoxia also exerts a hypophagia-independent effect on skeletal muscle mass loss. Chronic hypoxia and the UPS.…”
Section: Resultssupporting
confidence: 93%
“…It is noteworthy that similar results were obtained in EDL muscle (data not shown). Thus, in agreement with previous studies (4,33), these data show that hypoxia also exerts a hypophagia-independent effect on skeletal muscle mass loss. Chronic hypoxia and the UPS.…”
Section: Resultssupporting
confidence: 93%
“…Everest represented the opportunity to further GH AUC (mg/l min) investigate the endocrine and metabolic responses to prolonged exposure to extreme HA hypobaric hypoxia in association with physical exercise such as that performed by elite climbers. A large variety of factors, including environmental conditions, have been found to influence the hormonal response to exercise at HA (22,23) such as reduced oxygen availability, hypohydration, and alterations in nutritional homeostasis (24)(25)(26).…”
Section: Discussionmentioning
confidence: 99%
“…28 This change in taste sensation may be a factor in high-altitude anorexia, a self-induced starvation. 42 Animals 77 and humans 78 lose body weight when exposed to high-altitude conditions, due to reduced daily food intake and perhaps other factors. One study 78 found that hypoxia was associated with an 8.9% reduction in initial body weight, with appetite suppression and decreased caloric intake lasting for several weeks (during the study), particularly due to a decrease in carbohydrate preference, despite access to ample varieties and quantities of highly palatable foods.…”
Section: Vision Hearing and Tastementioning
confidence: 99%